MANAJEMEN LABA PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2020-2022 MELALUI PROFITABILITAS, LEVERAGE, DAN UKURAN PERUSAHAAN - Napiajo; Raihanah Beananda, Siti; Serini, Anjelina (Jurnal Ekonomi STIEP, 2023)
This analysis, which is a causal study, attempts to assess how three variables—firm size, profitability, and leverage—affect profits management strategies. The firm's total assets serve as a proxy for the firm size variable, while the debt-to-asset ratio (DAR) indicates leverage and return on assets (ROA) indicates profitability. Discretionary accruals are used to measure the management of earnings. The corporate financial report data used in this quantitative study approach was sourced from the Indonesia Stock Exchange (IDX) website. The mining businesses that were listed on the IDX between 2020 and 2022 made up the study's population. Purposive sampling was used in the sample selection process, yielding eight organizations as study samples with an observation length of three years. With the aid of the Statistical Package for Social Sciences (SPSS) version 22, multiple linear regression analysis was employed in this study's hypothesis testing. Descriptive statistical tests, traditional assumption tests (including multicollinearity, autocorrelation, heteroscedasticity, and normality tests), and hypothesis testing are all a part of the analysis process. The findings of the ANOVA test demonstrate that variables related to leverage, profitability, and company size all influence profits management strategies. Individual study findings, however, indicate that while firm size has no appreciable impact on earnings management, profitability and leverage do have a favorable and significant impact. Keywords: Profitability, Leverage, Company Size and Earnings Management